Agarose hydrogel-mediated electroporation method for retinal tissue cultured at the air-liquid interface - Megan L. Stone; Hannah H. Lee; Edward M. Levine (iScience)
Summary: It is advantageous to culture the ex vivo retina and other tissues at the air-liquid interface to allow for more efficient gas exchange. However, gene delivery to these cultures can be challenging. Electroporation is a fast and robust method of gene delivery, but typically requires submergence in liquid buffer for electrical current flow. We have developed a submergence-free electroporation technique that incorporates an agarose hydrogel disk between the positive electrode and retina. Inner retinal neurons and Müller glia are transfected with increased propensity toward Müller glia transfection after extended time in culture. We also observed an increase in BrdU incorporation in Müller glia following electrical stimulation, and variation in detection of transfected cells from expression vectors with different promoters. This method advances our ability to use ex vivo retinal tissue for genetic studies and should be adaptable for other tissues cultured at an air-liquid interface.